2022
DOI: 10.3389/fneur.2022.843871
|View full text |Cite
|
Sign up to set email alerts
|

Significance of D-Dimer in Acute Ischemic Stroke Patients With Large Vessel Occlusion Accompanied by Active Cancer

Abstract: BackgroundThis study aimed to investigate clinical outcome predictors of acute stroke patients with large vessel occlusion and active cancer and validate the significance of D-dimer levels for endovascular thrombectomy decisions.MethodsWe analyzed a prospectively collected hospital-based stroke registry to determine clinical EVT outcomes of acute stroke patients within 24 h with following criteria: age ≥18 years, NIHSS ≥6, and internal carotid artery or middle cerebral artery lesion. All patients were classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Preprocedural D-dimer levels did not differ significantly depending on successful recanalization [13,21,22]. Successful recanalization was conditionally more frequent only in patients with D-dimer levels above the threshold value of successful recanalization [13,23]. In this study, successful recanalization was not associated with preprocedural D-dimer levels; moreover, these levels did not significantly predict successful recanalization and showed unacceptable predictability.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Preprocedural D-dimer levels did not differ significantly depending on successful recanalization [13,21,22]. Successful recanalization was conditionally more frequent only in patients with D-dimer levels above the threshold value of successful recanalization [13,23]. In this study, successful recanalization was not associated with preprocedural D-dimer levels; moreover, these levels did not significantly predict successful recanalization and showed unacceptable predictability.…”
Section: Discussioncontrasting
confidence: 50%
“…Third, the prognostic value of preprocedural D-dimer levels has also been evaluated actively in cancer-related stroke. Higher D-dimer levels are consistently associated with unfavorable functional outcome after mechanical thrombectomy in patients with cancer-related stroke [21][22][23]. Because elevated D-dimer levels are a hallmark of cancer-related stroke, patients with higher D-dimer levels might have an underlying or hidden malignancy, which could have contributed to the unfavorable functional outcome in our study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Approximately 28.2% of patients with active malignancy recovered functional independence at 3 months, and it was only 1.7% higher than what was achieved in the non-EVT group of the HERMES37 Collaboration (26.5%). When comparing EVT with no EVT in patients with active malignancy, the non-EVT group showed worse functional outcome39 (15.6%) and higher mortality at 3 months (68.8%). Lee et al 29 reported that an unfavorable outcome was associated with increased serum D-dimer levels and higher baseline NIHSS score in patients with active malignancy after EVT.…”
Section: Discussionmentioning
confidence: 98%